Chia Seed (Salvia hispanica) Attenuates Chemically Induced Lung Carcinomas in Rats through Suppression of Proliferation and Angiogenesis - Naglaa A. Ali; Ghada H. Elsayed; Safaa H. Mohamed; Asmaa S. Abd Elkarim; Mohamed S. Aly; Abdelbaset M. Elgamal; Wael M. Elsayed; Samah A. El-Newary (MDPI AG, 2024)
In 2022, 2.5 million cases of lung cancer were diagnosed, resulting in 1.8 million deaths. These statistics have motivated us to introduce a new natural product which is feasible in lung cancer therapies. This comprehensive study was performed to study the effects of chia seed extracts (70% ethanol and petroleum ether) on lung cancer in vitro and in vivo models. The invitro cytotoxicity activity of the chia extracts was studied in lung cancer cell lines (A549 cells). After 48 h, chia alcohol and ether extracts showed more inhibitory influence (IC50, 16.08, and 14.8 µg/mL, respectively) on A549 cells compared to Dox (IC50, 13.6 µg/mL). In vivo, administration of chia alcohol and ether extracts (500 mg/kg/day, orally for 20 weeks) recovered 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung cancer, as a significant reduction in the lung cancer biomarkers, including the relative weight of the lung (20.0 and 13.33%), ICAM(31.73 and 15.66%), and c-MYC (80 and 96%) and MMP9(60 and 69%) expression genes, and improvement in these changes were observed by histopathological examinations of the lung tissues compared to the lung control. Chia seeds fought lung cancer via suppression of proliferation, angiogenesis, inflammation, and activation apoptosis. These activities may be attributed to the chemical composition of chia, which is identified by LC-Mass, such as caffeic acid, vanillic acid, kaempferol-3-O-glucuronide, and taxifolin. Finally, we can conclude that chia seeds have an anti-lung cancer effect with a good safety margin.